Feminism and Gender Stereotypes in the Short Story Anthology Perempuan Penakluk Ombak by the Rafflesia Writer Community - Rinda Ahtisyah (Yayasan Darussalam Bengkulu, 2023)
This study investigates the representation of feminism and gender stereotypes in the short story anthology Perempuan Penakluk Ombak authored by the Rafflesia Writer Community. Employing a qualitative content analysis within a library research framework, the study analyzed textual excerpts to identify depictions of women’s struggles, rights, and societal roles. The findings revealed 36 instances of feminist representation that highlight positive values such as equality in education, civil rights, freedom of expression, association, and economic participation. In contrast, 24 instances of stereotypes portrayed women as weak, dependent, or objects of violence. Furthermore, 61 moral messages were identified, offering didactic lessons on empathy, responsibility, respect for parents, and resilience. These results contribute to feminist literary criticism by showing how local literary works both challenge and reinforce patriarchal discourses. The study implies that literature can serve as a medium of cultural negotiation and social critique, though further comparative research with broader corpora is recommended.